Extraction of heterocyclic amines and polycyclic aromatic hydrocarbons from pork jerky and the effect of flavoring on formation and inhibition. (15th February 2023) - Lai, Y.W.; Lee, Y.T.; Cao, H.; Zhang, H.L.; Chen, B.H.
Highlights: QuEChERS based simultaneous extraction method was developed for PAHs and HAs. A high recovery of HAs by UPLC-MS/MS and PAHs by GC–MS/MS was shown. Roasting pork jerky at 220 °C generated more PAHs than at 180 °C, but unaffected HAs. Sugar addition reduced HAs & PAHs during roasting and soy sauce reduced some PAHs. Addition of 0.5% curcuma/cinnamon powder inhibited HAs formation, but not PAHs. Abstract: Heterocyclic amines (HAs) and polycyclic aromatic hydrocarbons (PAHs) are widely distributed in foods. This study aims to extract PAHs and HAs from pork jerky simultaneously by QuEChERS for analysis by GC–MS/MS and UPLC-MS/MS, respectively. Also,  the effects of flavoring materials and processing temperature on the formation of PAHs and HAs were studied. Acetonitrile containing 1% acetic acid possessed the highest extraction efficiency, with high accuracy and precision being attained for HAs and PAHs. Pork jerky roasted at 220℃ generated a higher PAHs content than 180℃, but unaffected the HAs formation. Addition of sugar reduced formation of both HAs and PAHs during roasting, while soy sauce reduced some PAHs and promoted HAs formation. Incorporation of 0.5% curcuma or cinnamon powder inhibited HA formation with a more pronounced effect being shown by the latter,  but neither inhibited PAH formation. The correlation between HA and PAH formation was assessed by principle component analysis.